Critical Medical Anthropology Perspectives in and from Latin America (University College London, 2020)
Critical Medical Anthropology presents inspiring work from scholars doing and engaging with ethnographic research in or from Latin America, addressing themes that are central to contemporary Critical Medical Anthropology (CMA). This includes issues of inequality, embodiment of history, indigeneity, non-communicable diseases, gendered violence, migration, substance abuse, reproductive politics and judicialisation, as these relate to health. The collection of ethnographically informed research, including original theoretical contributions, reconsiders the broader relevance of CMA perspectives for addressing current global healthcare challenges from and of Latin America. It includes work spanning four countries in Latin America (Mexico, Brazil, Guatemala and Peru) as well as the trans-migratory contexts they connect and are defined by. By drawing on diverse social practices, it addresses challenges of central relevance to medical anthropology and global health, including reproduction and maternal health, sex work, rare and chronic diseases, the pharmaceutical industry and questions of agency, political economy, identity, ethnicity, and human rights. 'Critical Medical Anthropology offers thought-provoking interventions to understandings of health, illness and healthcare. It extends a legacy of critical anthropological research, inviting and stimulating south-north dialogue, while generating inspiring new thinking at the intersections of health, social justice, human rights and political economy.'- Ciara Kierans, University of Liverpool